2022
DOI: 10.47391/jpma.4738
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory mediators as surrogates of malignancy

Abstract: Inflammation related to cancer occurs in the cellular vicinity of the tumour and is involved with predictions related to the course of disease and survival prognosis in varioua malignancies. These inflammatory markers affect different phases of tumourigenesis, i.e. carcinogenesis, tumour expansion, lymphovascular invasion, and distant metastasis, and, as a result, tumour cells can activate immune mediators and cells directly and/or chemokines as well as prostaglandins. Numbers of circulating different blood ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Indeed, findings indicate that these statistics could be utilized to forecast the outcome of a variety of disorders, including coronary heart disease, malignancies, and autoimmune disorders. 10 Multivariate logistic analysis was utilized to examine data from 153 cases of acute pulmonary embolism (PE) in a retrospective analysis, and it was concluded that NLR could be employed as a predictive marker determining 30-day death in pulmonary embolism. 11 Furthermore, it has been demonstrated that NLR may be employed as a measure of inflammatory responses to screen individuals contaminated with COVID-19 and can indicate poor outcome even during admission.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, findings indicate that these statistics could be utilized to forecast the outcome of a variety of disorders, including coronary heart disease, malignancies, and autoimmune disorders. 10 Multivariate logistic analysis was utilized to examine data from 153 cases of acute pulmonary embolism (PE) in a retrospective analysis, and it was concluded that NLR could be employed as a predictive marker determining 30-day death in pulmonary embolism. 11 Furthermore, it has been demonstrated that NLR may be employed as a measure of inflammatory responses to screen individuals contaminated with COVID-19 and can indicate poor outcome even during admission.…”
Section: Discussionmentioning
confidence: 99%